Morphological Study and Determination of M/E Ratio in the Bone Marrow of the Male Adult Ostriches (Struthio camelus) - Saeed Nazifi; Mina Tadjalli; Behrokh Marzban; Banafsheh Majidi (Journal of Basic & Applied Sciences, 2012)
Normal haematopoiesis, cellular components and M/E ratio in the bone marrow of the male adult ostriches (Struthio camelus)were studied. Bone marrow samples were collected from the proximal tibiotarsus bone of 10 healthy adult ostriches. The bone marrow smears were stained using the Giemsa stain. The results indicated that the development and formation of blood cells in the bone marrow of partridge were similar to other birds. The morphology of the cells was similar to chickens, ducks, quail, and black-head gull. The mean myeloid/erythroid (M/E) ratio was 1.02, the mean erythroid percentage was 47.38%, the mean myeloid percentage was 48.15%, the mean thrombocytic percentage was 3.52% and the mean percentage of all other cells percentage was 0.99%